The Implementation of Kahoot in Improving Students’ Tenses Understanding in Higher Education - Nurlaela, Nurlaela; Nawir, Syahrianti M (International Journal for Educational and Vocational Studies, 2020)
Tense is a part of English grammar that becomes something difficult to understand by students. Therefore, it needs interesting and creative learning media to face that problem. This research purposes to evaluate and analyze the implementation of Kahoot as a digital learning media in improving students’ understanding about tenses in higher education. There were 15 students in Civic Department of Education Faculty in Universitas Tompotika Luwuk as the sample of this research. Mix method in concurrent embedded strategy design was chosen as methodology of research. Quantitative data was collected through test, while qualitative data was collected by observation and interview. Hypothesis testing and descriptive analysis was conducted as analyzing technique. The quantitative result found that there was the improvement of students’ study result about tenses from pretest to posttest. The value of t-count (9,5176) which is greater than the value of t-table (2,048) is the proof. Moreover, quantitative result was supported by qualitative analysis result. It was proved by students’ achievement towards understanding indicators, namely translation, interpretation, and extrapolation. This research expected becomes contribution for the teachers and learners for implemented Kahoot as an interesting and creative learning media.